GUI for Continuous Integration and Automatic Bug Verification of Jenkins Server - Mali, Vaishnavi R; Surve, Anil R (International Journal of Computer Sciences and Engineering, 2019)
In software engineering, continuous integration (CI) is the routine with regards to blending all engineer working duplicates to a common mainline a few times each day. The principle point of CI is to avert coordination issues. Jenkins is a driving open source constant coordination server worked with Java. It is utilized to manufacture and test programming ventures constantly making it simpler to incorporate changes to the task. It provides more than 985 plugins to help to build and to test any project. Continuous Integration (CI) requires developers to integrate code into a shared repository several times a day. GUI will maintain all latest jobs with their build status and continuous notification referring to design issues, code, failures, etc. Once the project is configured in Jenkins then all future builds are automated. Hence GUI will help to represent basic reporting like run status (successful, failure, unstable) and weather reports (job health). GUI will also provide automatic continuous regression run which will give flag details of new relevant changes in build compared to last run and easy access for code change mapping and auto-selection. GUI will help to eliminate manual verification.